Diversified Strategies for the Synthesis of Bifunctional Dendrimeric Structures. Issue 24 (10th July 2013) - Riegert, David; Pla‐Quintana, Anna; Fuchs, Sabine; Laurent, Régis; Turrin, Cédric‐Olivier; Duhayon, Carine; Majoral, Jean‐Pierre; Chaumonnot, Alexandra; Caminade, Anne‐Marie
Abstract: The synthesis of three new families of dendrimeric compounds possessing two different types of functions is reported. These functions are triethoxysilyl group(s), potentially suitable for grafting onto materials, in particular silica, and primary amines (in their protected form), potentially suitable for trapping CO2 . All these dendrimeric compounds are based on phosphorus dendrimers, and possess either one Si(OEt)3 group at the core of dendrons or of "off‐centre" dendrimers, or several Si(OEt)3 groups precisely placed on half of the terminal groups. These compounds are characterized by 31 P NMR spectroscopy, which affords precious information on the structure, confirmed, in one case, by the X‐ray diffraction structure of a first‐generation dendrimer. Abstract : The synthesis of three families of new, bifunctional dendrimeric compounds is reported. The types of functional groups used here are particularly suitable for grafting these compounds onto materials, but the strategies elaborated for their syntheses are potentially useful for many different types of couples of functional groups.